Evaluación de la calidad del servicio de atención al usuario del MIES en personas con capacidades especiales, cantón Chone - Solórzano Pazmiño, Nuglo Jorge (2021)
The present research work was carried out in order to evaluate the quality of the care service provided by the Ministry of Economic and Social Inclusion (MIES) of the Chone canton to people with special abilities to improve internal administrative processes, in the study they were established Scientific and legal theories that provided support for the research, methods such as synthetic analytical, inductive and deductive that allowed the efficient development of activities and the services provided by the MIES were described as: Attention to the home and the community, inclusion to cash transfer benefit, co-responsibility monitoring, discount networks, funeral services, retirement pension, credits and assistance in case of contingencies. In the study, an instrument was applied to collect data, composed of a survey designed under a Likert scale and directed to people with special abilities. The results obtained determined that the physical facilities must be improved, that the assigned budget does not allow to cover the demand for attention to the services provided by the institution. Finally, the conclusions of the study lead to the elaboration of an improvement proposal, through the following actions: managing the purchase of equipment and materials to meet the requirements of users with special abilities, training staff in relation to the services provided by the MIES, suggest an increase in the budget to meet each of the users' requirements.